2018
DOI: 10.1002/brb3.1103
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal alcohol exposure affects brain function during place learning in a virtual environment differently in boys and girls

Abstract: IntroductionAlthough performance deficits in place learning have been reported in fetal alcohol spectrum disorders (FASD), neural correlates of these deficits have not been investigated. This functional magnetic resonance imaging (fMRI) study of 57 children (41 alcohol‐exposed; 16 controls; mean age = 9.4 years; 29 boys) examined effects of prenatal alcohol exposure (PAE) on place learning in a virtual environment, the computer‐generated (CG) arena.MethodsFunctional magnetic resonance imaging data were acquire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 118 publications
(173 reference statements)
0
7
0
Order By: Relevance
“…Whereas right hippocampal volume was a mediator when either FASD diagnostic group or binge exposure group was used as the IV, ICV was not a significant mediator of either effect on VWM performance, indicating that the observed mediation is not attributable to smaller overall brain size. These findings show that hippocampal volume partially mediates the effect of PAE on spatial navigation, although other brain regions that have also been found to be active during spatial navigation, such as the parahippocampal gyrus (Parslow et al, 2004; Woods et al, 2018) and frontal cortex (Hsu et al, 2000), likely also contribute to this effect.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Whereas right hippocampal volume was a mediator when either FASD diagnostic group or binge exposure group was used as the IV, ICV was not a significant mediator of either effect on VWM performance, indicating that the observed mediation is not attributable to smaller overall brain size. These findings show that hippocampal volume partially mediates the effect of PAE on spatial navigation, although other brain regions that have also been found to be active during spatial navigation, such as the parahippocampal gyrus (Parslow et al, 2004; Woods et al, 2018) and frontal cortex (Hsu et al, 2000), likely also contribute to this effect.…”
Section: Discussionmentioning
confidence: 79%
“…However, the validity of our alcohol use ascertainment techniques has been demonstrated in relation to fatty acid ethyl ester metabolites in meconium (Bearer et al, 2003). Additionally, the predictive validity of the timeline follow‐back has been shown in relation to infant and child cognition (Jacobson et al, 2002, 2008; Lewis et al, 2016), somatic growth (Carter et al, 2016), and brain structure (De Guio et al, 2014; Fan et al, 2016; Jacobson et al, 2017; Meintjes et al, 2014) and function (Woods et al, 2015, 2018). Nutritional differences might have contributed to these effects, but alcohol consumption during pregnancy was not associated with differences in maternal diet or anthropometric measures in this population (Carter et al, 2017), indicating that poor nutrition among the drinkers is unlikely to play an important role in the extensively reported effects of PAE on growth and neurobehavior, including performance on the VWM.…”
Section: Discussionmentioning
confidence: 99%
“…While we included gender in our models, we found no impact of gender on our subgroup analysis at either the sensor or source level. The lack of gender effects in the current study may indicate that basic neurophysiological disruptions produced by PAE detected in a resting-state task are not as sensitive to gender effects as specific modalities of cognitive testing, that is, spatial memory and spatial navigation (Dodge et al, 2019;Woods et al, 2018). However, the current sample included children 8 to 12 years of age which may have avoided potential puberty confounds.…”
Section: Discussionmentioning
confidence: 81%
“…In experimental animal models, GABA receptor hyperactivation inhibits the release of glutamate and dopamine, thereby reducing the levels of other neurotransmitters linked to behavior modulation through its ability to regulate cognitive function. Further, studies showed that alterations in the expression of GABA receptors in animals impairs memory function [ 102 , 103 ], and prenatal alcohol exposure can chronically alter brain development and function in the offspring [ 104 ]. One study on cortical plate samples from fetal and infant brains demonstrated insufficient and delayed production of GABAergic interneurons in the ganglion during the two first trimesters of pregnancy and their delayed incorporation into the laminar structures of the frontal cortex, as well as mispositioning of GABAergic and calretininergic interneurons throughout fetal life [ 105 ].…”
Section: Activation Of the Gaba Receptor In The Cns Of The Fetus In R...mentioning
confidence: 99%